(untitled) (Agricultural Engineering, 2016)
The objective of the paper was to investigate the impact of the plate diameter on the value of the measured pre-compaction stress of soil. The investigations were carried out on model samples with 100 mm diameter and 30 mm height made of the silt loam and the percentage moisture content of 13.7 and 21.9%. The following properties of the used material were measured: the granulation group, density of solid particles, humus content, reaction, plastic and liquid limit and the degree of saturation of samples. The samples were loaded with a testing machine using plates with varied diameters: 20, 30, 50, 70, 80, 90, 96, 98 and 99 mm. The pre-compaction stress value was measured with the method of searching for the crossing point of tangents with the secondary stress curve and original stress curve (a classic method). It was found out that for samples with saturation amounting to 13.7% of the moisture content the pre-compaction stress does not significantly depend on the plate diameter. For samples with saturation amounting to 21.9% of the moisture content the precompaction stress may significantly depend on the plate diameter. Based on the obtained results a conclusion was made that in the research on the pre-compaction stress with the method of uni-axial deformations, the relation of the plate diameter (d) to the diameter of the cylinder (D)) should be within 0.3 ≤ d/D < 0.8.